Penguatan Karakter Disiplin Siswa Melalui Peranan Guru Di Sekolah Dasar - Sri Suwartini; Aprilia Tri W; Yulinda Sari; Nur Amelia Sari; Rahmi Adiffa S. A (CV. ITTC INDONESIA, 2024)
As a learning institution, schools are responsible for forming the character of students. To achieve this, teachers play an important role in trying to increase the level of behavior through rules that reinforce learning. This research was conducted with the aim of knowing and describing the role of teachers in implementing elementary school student behavior. This research uses an effective method to examine the role of teachers in facilitating the development of expert opinions by using descriptive methods by describing the research of several experts and then unpacking it. The data collection method in this research uses library research in which researchers collect data by studying, reviewing and analyzing national and international journals, books and articles by previous researchers related to the research topic. The research results show that teachers play an important role in improving student learning, making students familiar with all the rules and preventing disciplinary problems.